Design, Synthesis and Biological Evaluation of Novel Ketamine Derivatives as NMDAR Antagonists - Shiyun Li; Bin Wen; Wei Zhao; Lulu Wang; Xingquan Chen (Molecules, 2024)
Depression is a chronic, severe, and often life-threatening neurological disorder. It not only causes depression in patients and affects daily life but, in severe cases, may lead to suicidal behavior and have adverse effects on families and society. In recent years, it has been found that sub-anesthetic doses of ketamine have a rapid antidepressant effect on patients with treatment-resistant depression and can significantly reduce the suicidal tendencies of patients with major depressive disorder. Current studies suggest that ketamine may exert antidepressant effects by blocking NMDAR ion channels, but its anesthetic and psychotomimetic side effects limit its application. Here, we report efforts to design and synthesize a novel series of ketamine derivatives of NMDAR antagonists, among which compounds 23 and 24 have improved activity compared with ketamine, introducing a new direction for the development of rapid-acting antidepressant drugs.